Logical and gnoseological features of diagnosis - A. K. Sukhotin (Бюллетень сибирской медицины)
A diagnosis, as a type of getting knowledge (alongside with science and education) goes from consequences to a reason (from symptoms to nosological unit), this determines it’s hypothetical character. There is a choice amongst variants, exposed by method of differential diagnosis, which is been realized on the ground of logical operations of moving out hypothesises and constructing analogies. Though a diagnosis don’t carries a new knowledge, it presents a creative process, which is been understood as carring out the essential human sorces in their full realization (the basic creative law).